Relationship between the Responsiveness of Service Providers with Patient Satisfaction at Three Conventional Radiography Services in Denpasar - Cokorda Istri Ariwidyastuti; Pande Putu Januraga; Dyah Pradnyaparamita Duarsa (Universitas Udayana, 2016)
Background and purpose: Patient satisfaction, including on radiography services, is an important component of health care provision. Surveys on patient satisfaction have been carried out particularly in government hospitals, but a more detailed study to determine the relationship between patient satisfaction with the responsiveness of service providers has yet to be carried out. This study aims to determine the relationship between the six domains of responsiveness of service providers and outpatient satisfaction at three conventional radiography facilities in Denpasar. Methods: Study was conducted by cross-sectional survey of 158 respondents selected consecutively in three conventional radiography services, namely a government hospital, a private hospital and a private radiology clinic. Data were collected through interviews using modified questionnaires on responsiveness from WHO. Data were analyzed by univariate, bivariate (chi-square test) and multivariate logistic regression method. Results: Univariate analysis indicated that patient satisfaction was 69% but still below the minimum service standards (>80,0%). Multivariate analysis showed that factors associated with satisfaction were the domain of attention (AOR=3.77; 95%CI: 1.62-8.76), the quality of infrastructure (AOR=4.57; 95%CI: 1.61-12.93) and communication (AOR=6.30; 95%CI: 1.75-22.64). Conclusion: Patient satisfaction was generally still below the standard. Domains of responsiveness associated with patient satisfaction were the quality of infrastructure, level of attention and communication skills of service providers.